The European Union's fishing activity outside of European waters and the Sustainable Development Goals - Johnson, Andrew Frederick; Lidström, Susanna; Kelling, Ingrid; Williams, Chris; Niederműller, Simone; Poulsen, Katrin Vilhelm; Burgess, Samantha; Kent, Rhona; Davies, William (Fish and fisheries (Oxford, England), 2021)
The EU's fishing fleet engages in extensive fishing activities in the Exclusive Economic Zones of non‐EU countries as well as in areas beyond national jurisdiction. These activities are regulated by an external dimension in the EU's Common Fisheries Policy (CFP). We review the relationship between the CFP, including regulations for the Sustainable Management of External Fishing Fleets (SMEFF) and the role of Sustainable Fisheries Partnership Agreements (SFPAs) and Regional Fisheries Management Organisations (RFMOs), and the internationally agreed aims and definitions of sustainability provided by the United Nations Sustainable Development Goals (SDGs). The SDG that most directly relates to fish and fisheries is goal 14, to "conserve and sustainably use the oceans." This paper, however, focuses on relationships between the CFP and SDGs that target social and economic dimensions, including those aiming to eliminate poverty (1) and hunger (2), improve health (3), provide decent work and economic growth (8), and achieve gender equality (5) and peaceful institutions (16). We identify several areas where the EU's external fishing fleet interacts with different facets of those goals, and suggest some important improvements that can be made to support the development of the EU’s external fleet into a contributor, rather than counterforce, to sustainable development in line with commitments under Agenda 2030. We provide a first and broad overview of an important area for future interdisciplinary research. We conclude by identifying specific questions that can provide starting points for further in‐depth analyses of the sustainability of EU fishing activities in external waters.